2014
DOI: 10.1097/qai.0000000000000209
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Tuberculosis Among HIV-Infected Pregnant Women in Lesotho

Abstract: Implementation of ACF and IPT is feasible within the MCH setting. Uptake of IPT during pregnancy among HIV-positive women was high, but with a high rate of loss to follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In addition, enhancing the availability and accessibility of RNTCP facilities in hard-to-reach Adivasi (tribal) areas, where case detection rates are very low, may help to reduce the proportion of India’s population without access to TB care [31]. Finally, various strategies of targeted active case finding—especially higher yield strategies focused on repeated screening of household contacts of known TB patients [79], people living with HIV [80,81], and individuals visiting health care facilities [82]—may also help to substantially reduce Gap 1a/1b by identifying patients who may otherwise not seek TB care or do so with substantial delay [83]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, enhancing the availability and accessibility of RNTCP facilities in hard-to-reach Adivasi (tribal) areas, where case detection rates are very low, may help to reduce the proportion of India’s population without access to TB care [31]. Finally, various strategies of targeted active case finding—especially higher yield strategies focused on repeated screening of household contacts of known TB patients [79], people living with HIV [80,81], and individuals visiting health care facilities [82]—may also help to substantially reduce Gap 1a/1b by identifying patients who may otherwise not seek TB care or do so with substantial delay [83]. …”
Section: Discussionmentioning
confidence: 99%
“…A small study of IPT among pregnant women in Lesotho reported a lower proportion of IPT completion (64.5%) [14], probably due the high postpartum dropout that has been well documented among HIV-infected pregnant women [15]. …”
mentioning
confidence: 99%
“…Among these, research on maternal and child health quality of care, viral load point-of-care devices, and infant point-of-care diagnoses had hardly any publications in the high-priority research category. In addition, research on epidemiology of non-communicable diseases in people living with HIV [41], uptake and effectiveness of isoniazid preventive therapy for opportunistic tuberculosis infection [42], and discordant transmission of HIV in couples [20, 43, 44] had the least number of publications in the same category. Moreover, research on epidemiology of tuberculosis in children [4548] and impact of HIV on the national health system [20, 4952] had a low number of publications in the high-priority research category.…”
Section: Resultsmentioning
confidence: 99%